Double Jeopardy: The Effect of Multiple Secondary Trauma Exposure on Subjective Age. Issue 3 (3rd April 2019) - Bachem, Rahel; Scherf, Johanna; Levin, Yafit; Solomon, Zahava
Abstract: The present study investigates whether secondary traumatization (i.e., family history of Holocaust survival and secondary exposure to captivity) is implicated in subjective age. Women exposed to different levels of secondary traumatization ( N  = 177) were assessed. Analyses of variance (ANOVAs) revealed that a Holocaust background and husband's captivity had a marginally significant positive effect on age appearance. Women with a Holocaust background whose husbands were held captive reported older interest age, indicating double jeopardy for older subjective age when two sources of secondary traumatization are present. A similar trend existed for behavior age. Possible explanations for these complex findings of risk and resilience are discussed.